Answer:
30/10=10/3
Step-by-step explanation:
because 10/3 if you multiply 3 times 10 and keep 10 and switch it around you'll get 30/10
Answer:
3 - (n - 1) = 1/2(3n - 4)
Step-by-step explanation:
We want to write three minus the difference of a number and one equals one-half of the difference of three times the same number and four as an equation.
Let the number be n.
The first part is: three minus the difference of a number and one:
3 - (n - 1)
The second part is: one-half of the difference of three times the same number and four:
1/2(3n - 4)
Now, let us equate the first and second parts:
3 - (n - 1) = 1/2(3n - 4)
PS: I really do not understand the options
Thanks. I’m not struggling or anything but thanks for the kind words.
Answer:
D
Step-by-step explanation:
Because they are opposite of each other
you must substitute x in the equation given :)
examples:
when x is -2
therefore, y = 2(-2) + 3
y = -1
when x is 0
therefore, y = 2(0) + 3
y = 3
when x is 1
therefore, y = 2(1) + 3
y = 5
when x is 3
therefore, y = 2(3) + 3
y = 9
for (b) you only have to plot based on the table ;)
hope this helps